CPP-ACP complex as a solution to the problem of complications after teeth bleaching - a literature review - Łucja Kula; Katarzyna Mocny-Pachonska (Kazimierz Wielki University, 2022)
Introductions and purpose: Teeth bleaching is an increasingly popular procedure that comes with its specific set of complications including damaged enamel, dentin hypersensitivity, and increased vulnerability to bacterial colonization. CPP-ACP complex possesses remineralizing and bacteriostatic properties as well as the ability to abolish dentin hypersensitivity. The aim of this study is to systematise the state of current knowledge on the use of casein phosphopeptide with amorphous calcium phosphate in combating complications after tooth bleaching. Description of the state of knowledge: The CPP-ACP complex used alone or in a protocol with a bleaching agent, in a way that is comparable to other products, abolishes post-operative dentin hypersensitivity by blocking the flow of dentino-pulpal tubular fluid. It restores the morphological properties of the tooth, by increasing the hardness of the bleached enamel, more effectively than fluoride agents. Casein phosphopeptide with amorphous calcium phosphate limits the penetration of the bleaching agent into the tooth chamber, thereby preventing the development of pulp inflammation. Moreover, because of its buffering properties, it prevents the development of caries on surfaces weakened by the bleaching process.